Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, David; Kraus, Martin; Merklein, Marion (Sheet Metal 2021, 2021)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressin
Keywords: joining by forming; multi-metal-systems; pin forming; pin joining